2018
DOI: 10.1177/1945892418816841
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Middle Turbinectomy on Airflow to the Olfactory Cleft: A Computational Fluid Dynamics Study

Abstract: Background The impact of middle turbinate resection (MTR) on olfaction remains a point of debate in the current literature. Few studies have objectively evaluated olfactory cleft airflow following MTR; thus, the mechanism by which MTR may impact olfaction is poorly understood. It is not known whether the postsurgical changes in airway volume, flow, and resistance increase odorant transport or disrupt the patterns of normal airflow. Computational fluid dynamics can be used to study the nasal airway and predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
(35 reference statements)
2
22
0
Order By: Relevance
“…This suggests that the relationship between airflow distribution, regional airflow rate, and regional resistance may be exceedingly complex, and are important factors to consider when designing, implementing, or selecting implants for patients with ENS symptoms. This distribution of airflow in the presence of cotton placement is comparable with previous CFD results from healthy controls, and cotton parameters, such as volume and position, should be further explored to characterize its impact on optimizing the distribution of nasal airflow.…”
Section: Discussionsupporting
confidence: 81%
“…This suggests that the relationship between airflow distribution, regional airflow rate, and regional resistance may be exceedingly complex, and are important factors to consider when designing, implementing, or selecting implants for patients with ENS symptoms. This distribution of airflow in the presence of cotton placement is comparable with previous CFD results from healthy controls, and cotton parameters, such as volume and position, should be further explored to characterize its impact on optimizing the distribution of nasal airflow.…”
Section: Discussionsupporting
confidence: 81%
“…Alam et al 9 applied computational fluid dynamics to evaluate the functional impact of middle turbinate resection in a virtual model on nasal airflow, resistance, and olfaction. Their results suggest that middle turbinate resection generally appears to increase nasal airflow while decreasing nasal resistance and may result in increased airflow to the olfactory region although this was variable within their data set.…”
Section: Thementioning
confidence: 99%
“…There have been extensive computational studies investigating different nasal surgeries and their effect on nasal airflow (Xiong et al, 2008;Rhee et al, 2011;De Wang et al, 2012;Frank et al, 2013a;Hariri et al, 2015;Dayal et al, 2016;Maza et al, 2019;Inthavong et al, 2019;Siu et al, 2020a), which showed the ability of virtual surgery to guide surgical interventions to alleviate nasal airway obstruction. Previous CFD studies of middle turbinate resection (Zhao et al, 2014;Alam et al, 2019;Lee et al, 2016) have demonstrated shifts in airflow toward the area of middle turbinate resection and decreased airflow velocity, decreased wall shear stress, and increased local air pressure. Chen et al (2012) found that following functional endoscopic sinus surgery, a moderate inspiratory airflow rate and a particle diameter of approximately 10µm improved intranasal deposition into the maxillary sinuses.…”
Section: Introductionmentioning
confidence: 96%